Local ecological knowledge provides important conservation guidelines for a threatened seahorse species in mangrove ecosystems - Ternes, Maria Laura Fontelles; Freret-Meurer, Natalie V.; Nascimento, Rodolfo Leandro; Vidal, Marcelo Derzi; Giarrizzo, Tommaso (Frontiers in Marine Science, 2023)
Local Ecological Knowledge and social perceptions of human communities that depend on natural resources can provide important baseline information on local threats and impacts at a fine scale for conservation management. Seahorses play important economic role in Brazilian mangroves, being sought-after for seahorse-watching tours. This touristic activity is not yet formally regulated and our work is a contribution to seahorse-watching management at three study sites located in two Marine Protected Areas (MPAs) – Jericoacoara National Park, and Delta do Parnaíba Environmental Protection Area – in the Brazilian northeast states of Ceará, Piauí, and Maranhão. Through semi-structured interviews, we investigated the perception of seahorse-watching operators regarding seahorse abundance, local threats, and conservation insights in mangrove ecosystems. We interviewed all 38 existing informants at the study sites. Approximately half of the informants rely exclusively on seahorse-watching as an income source. Overall, 55.3% highlighted declines in seahorse abundance, 100% believed that seahorses are threatened with extinction. Silting (57.9%), fishing (55.3%), and pollution (37%) were cited as main threats to seahorses and mangroves. Among the proposed conservation actions, environmental surveillance (57.9%), zoning (26.3%), education (26.3%) were the most cited. Respondents support the MPAs but would like to see greater engagement of management institutions towards the communities, considering their local needs. Some differences in perception between communities reflect local realities and social contexts, which should be considered for conservation and management effectiveness. Our study contributes supporting this approach, as local scale studies on social perceptions can improve conservation and local management, especially for data-poor species.